In Situ Deposition of Drug and Gene Nanoparticles on a Patterned Supramolecular Hydrogel to Construct a Directionally Osteochondral Plug - Kang, Jiawei; Li, Yaping; Qin, Yating; Huang, Zhongming; Wu, Yifan; Sun, Long; Wang, Cong; Wang, Wei; Feng, Gang; Qi, Yiying (Nano-Micro Letters, 2023)
The integrated repair of bone and cartilage boasts advantages for osteochondral restoration such as a long-term repair effect and less deterioration compared to repairing cartilage alone. Constructing multifactorial, spatially oriented scaffolds to stimulate osteochondral regeneration, has immense significance. Herein, targeted drugs, namely kartogenin@polydopamine (KGN@PDA) nanoparticles for cartilage repair and miRNA@calcium phosphate (miRNA@CaP) NPs for bone regeneration, were in situ deposited on a patterned supramolecular-assembled 2-ureido-4 [lH]-pyrimidinone (UPy) modified gelation hydrogel film, facilitated by the dynamic and responsive coordination and complexation of metal ions and their ligands. This hydrogel film can be rolled into a cylindrical plug, mimicking the Haversian canal structure of natural bone. The resultant hydrogel demonstrates stable mechanical properties, a self-healing ability, a high capability for reactive oxygen species capture, and controlled release of KGN and miR-26a. In vitro, KGN@PDA and miRNA@CaP promote chondrogenic and osteogenic differentiation of mesenchymal stem cells via the JNK/RUNX1 and GSK-3β/β-catenin pathways, respectively. In vivo, the osteochondral plug exhibits optimal subchondral bone and cartilage regeneration, evidenced by a significant increase in glycosaminoglycan and collagen accumulation in specific zones, along with the successful integration of neocartilage with subchondral bone. This biomaterial delivery approach represents a significant toward improved osteochondral repair. Highlights: 1 A multifactorial and oriented scaffolds was constructed to stimulate osteochondral regeneration. 2 This is the first demonstration that both drug and gene nanoparticles were spatially deposited on a patterned film through metal-ligand interactions. 3 For the first time, film-rolling approach was employed to construct osteochondral plug to mimick the Haversian canal structure of natural bone.